Prevalence and antimicrobial resistance of Salmonella in livestock and humans in Korogocho and Viwandani slums - Gichuyia, M.C. (University of Nairobi, 2016)
Salmonella species cause significant morbidity, mortality and burden of disease globally. In Kenya, salmonellosis is only second to pneumococcal disease as a leading cause of mortality in children under five; children living in the slums are especially vulnerable. Being a multihost zoonotic pathogen, it is important to understand its epidemiology in various hosts so as design effective control strategies.